Does Border Enforcement Protect U.S. Workers from Illegal Immigration? - Hanson, Gordon H.; Robertson, Raymond; Spilimbergo, Antonio (The Review of Economics and Statistics, 2002)
In this paper, we examine the impact of enforcement of the U.S.-Mexico border on wages in U.S. and Mexican border regions. The U.S. Border Patrol polices U.S. boundaries, seeking to apprehend any undocumented entrants. It concentrates its efforts on the Mexican border. We examine labor markets in border areas of California, Texas, and Mexico. For each region, we have high-frequency data on wages and person-hours the U.S. Border Patrol spends policing the border. For a range of empirical specifications and definitions of regional labor markets, we find little impact of border enforcement on wages in U.S. border cities and a moderate negative impact of border enforcement on wages in Mexican border cities. These findings are consistent with two hypotheses: border enforcement has a minimal impact on illegal immigration, and illegal immigration from Mexico has a minimal impact on wages in U.S. border areas.